Tetraploa lignicola, a new freshwater fungal species from Yunnan Province, China - Li, Jia-Ning; Wang, Shi-Yu; Xu, Rong-Ju; Xu, Ke; Ma, Chun-Hua; Zhao, Qi; Zhu, Ying-An (Phytotaxa, 2023)
Two fungal strains were isolated from submerged decaying woods in the freshwater habitats, which are characterized by cylindrical, septate, verrucose, brown conidia, composed of four vertical columns of cells, 3-septate in each column, with four appendages at the base which are slightly tapering toward the apex and each with 5–10-septate. Multigene phylogenetic analyses of combined ITS, LSU, and SSU sequences data showed that the two isolates clustered into a separated clade in Tetraploa. Herein, we report it as a new hyphomycetous species, Tetraploa lignicola. The descriptions, illustrations, and a phylogenetic tree show the placement of T. lignicola, the comparisons between the new species and other morphologically similar taxa in Tetraploa are also provided.